Macula Retinal Vasculitis and Choroiditis Associated With Granulomatosis With Polyangiitis - Lim, Lik Thai; Vasudevan, Vinaya; Shelton, Julie B.; Vitale, Albert T.; Moorthy, Ramana S N (Lippincott Williams and Wilkins, 2017)
Purpose:To report a case series of two cases of granulomatosis with polyangiitis, previously known as Wegener granulomatosis, which developed macular necrosis, not previously associated with granulomatosis with polyangiitis, healed with fibrosis, despite aggressive immune-modulating therapy and good control of systemic disease.Methods:Case series of two cases with observation of treatment progress.Results:The results reported the progress of response to treatment in the two cases, which resulted in the final outcome of fibrosis in the macula region, despite being on aggressive immune-modulating therapy and good systemic control.Conclusion:Granulomatosis with polyangiitis can be associated with macular necrosis leading to fibrosis, unresponsive to immune-modulating therapy.